A Prospective, Randomized Clinical Trial to Evaluate Analgesic Efficacy of Bilateral Pterygopalatine Fossa Injection in Patients Undergoing Maxillofacial Cancer Surgeries Under General Anesthesia. Issue 1 (1st January 2021) - Abdelghafar, Ekramy M; Abbas, Dina Nabil; Othman, Ahmed; Zayed, Sherif Bahaa Elddin; Shawki, Ashraf Hamed
ABSTRACT: Objective : Evaluation of the analgesic efficacy and safety of ultrasound-guided pterygopalatine fossa (PPF) block in patients undergoing maxillofacial cancer surgeries under general anesthesia. Methods: Forty-eight patients scheduled for maxillofacial cancer surgeries enrolled in the study were randomly allocated into group (A): ultrasound-guided bilateral PPF block using local anesthetic; and group (B): ultrasound-guided bilateral PPF injection with saline. Our primary outcome was assessing postoperative analgesia using visual analog scale and the amount of nalbuphine used for rescue analgesia. We recorded the operative field's quality, end-tidal sevoflurane concentration, the total amount of nitroglycerin used to achieve the target mean arterial pressure (MAP) of 60–65 mmHg, the frequency of propranolol usage, emergence time and Aldrete score. Results: The VAS score was significantly lower in group A than group B until the 18th postoperative hour ( P < 0.0001). The number of patients required nalbuphine (12 versus 24 patients) and total nalbuphine doses were significantly less in group A (10 ± 2 mg) versus group B (20 ± 5 mg) ( P < 0.01). Sevoflurane mean end-tidal concentration was significantly less in group A (2.2 ± 0.53%) than in Group B (2.7 ± 0.48%), P -value = 0.019. Total nitroglycerine dose was significantly lower (2.45 ± 0.63 µg/kg/min) in group A than (3.58 ± 0.77 µg/kg/min) in group B ( P value<0.05). Conclusions: ultrasound-guided PPF block combined with general anesthesia is a safe technique and helps in providing better operative field by adequate control over the blood pressure. It is effective for decreasing the postoperative pain and analgesic requirements in patients undergoing maxillofacial cancer surgery.